Tribological characteristics of a cemented carbide friction surface with chevron pattern micro-texture based on different texture density. (February 2020) - Dan, Li; Xuefeng, Yang; Chongyang, Lu; Jian, Cheng; Shouren, Wang; Yanjun, Wang
Abstract: The influence of the drawing area on the tribological properties was studied using femtosecond laser processing of four kinds of chevron pockets of cemented carbides with 5.05%, 9.5%, 13.02%, and 15.2% texture density. The results show that the chevron pattern texture with a certain texture density helps decrease the friction of a YT15 cemented carbide surface compared with un-textured specimens. This surface texture minimizes and stabilizes the friction coefficient, while the fluid dynamic pressure increased in the specimen with 9.5% texture density. Wear occurs due to abrasive and adhesive wear. Therefore, designing a reasonable shape and selecting appropriate texture density will be the focus of further research on surface micro-texture. Graphical abstract: Image 1 Highlights: Chevron pattern micro texture can improve the friction performance of hard alloy. Chevron pattern micro texture has hydrodynamic effect on friction surface with oil. 9.5% texture density has better hydrodynamic effect. The main wear form is abrasive wear and adhesive wear.